Relationship Between Electronic Device Usage with Asthenopia in Workers at Pelita Harapan University Lippo Karawaci - Sachio Harlendo; Josiah Irma; Saraswati Anindita Rizki; Ruth Syeela Widianty (Medicinus, 2026)
Background: Breast cancer is the most common malignancy among women and a leading cause of cancer-related mortality. Early detection is crucial to improve survival outcomes. Mammography is considered the gold standard for screening women over 40 years, while ultrasonography (USG) is frequently used in younger women with dense breasts. However, diagnostic accuracy varies, and comparative studies in Indonesia remain limited. To compare the diagnostic accuracy of mammography and ultrasonography in differentiating benign and malignant breast lesions using histopathology as the Gold standard.   Methods: This cross-sectional analytic study included 91 patients who underwent mammography, ultrasonography, and histopathological confirmation at MRCCC Siloam Semanggi Hospital. Diagnostic parameters including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), accuracy, and area under the curve (AUC) were calculated. Statistical analysis used McNemar’s test and ROC curve analysis based on Hanley & McNeil’s method, with p < 0.05 considered significant.   Result: Ultrasonography demonstrated higher sensitivity (98.4%) and NPV (92.3%) than mammography (96.7% and 88.9%), indicating better ability to rule out malignancy. Mammography showed higher specificity (53.3% vs. 40.0%) and PPV (80.8% vs. 76.9%), reflecting better performance in identifying benign lesions. Overall accuracy was slightly higher for mammography (82.4%) compared to USG (79.1%). The AUC for mammography was 0.750 (95% CI: 0.630–0.870), while USG had an AUC of 0.692 (95% CI: 0.565–0.819). Overlapping confidence intervals indicated no statistically significant difference in diagnostic accuracy between the two modalities (p > 0.05).   Conclusions: Mammography and ultrasonography both demonstrated high diagnostic performance with complementary strengths. Mammography provided higher specificity and PPV, while USG offered superior sensitivity and NPV. Given the small difference in accuracy and overlapping AUC confidence intervals, no significant difference was found between the two modalities. Combined use of mammography and USG may improve diagnostic accuracy in clinical practice.